The Development of A Hotel Room Reservation Application Using The Laravel Framework at Abadi Hotel - Halim, Abdul; Rohman, Ali; Ifvochy, James (ARRUS Journal of Engineering and Technology, 2025)
The rapid development of information technology has prompted various industries, including the hospitality sector, to adapt to digital services. Hotel Abadi, as a provider of accommodation services, requires a web-based room booking system to enhance operational efficiency and customer convenience. This study aims to develop a hotel room reservation application using the Laravel framework, a modern PHP framework known for its security features, MVC structure, and database management capabilities. The system development method used is the Waterfall model, consisting of requirement analysis, system design, implementation, testing, and maintenance phases. Data were collected through direct observation, interviews with hotel management, and documentation of the conventional booking process. The main features developed in the application include: room search, room reservation, payment confirmation, customer data management, and transaction reporting. The testing results show that the application operates according to the expected functionalities. Users can independently book rooms without having to visit the hotel in person. The system also facilitates real-time management of booking and payment data for the hotel administration. With this application, Hotel Abadi is expected to improve service quality and competitiveness in the digital era. This Laravel-based room reservation application contributes significantly to the digital transformation in the hospitality sector, especially for medium-scale hotels that still rely on manual processes.